A qualitative analysis on transfer pricing tax audit performance in Indonesia - Faisal Labib Zulfiqar; I Gusti Ketut Agung Ulupui; Dwi Kismayanti Respati (LPMP Imperium, 2023)
This study is qualitative research using inductive reasoning through documentation and literature studies. The finding showed seven areas of dispute: gross income-related items, purchase cost, intra-group services, royalty, dividend, interest expense, and interest income. Furthermore, it concluded that documentation, comparable data, and comparability method were the three main issues in transfer pricing disputes. Ultimately, it showed that the tax court decree was dominated by decrees that favored taxpayers’ appeals. Public interest statement Tax disputes are known for their lengthy and costly process, but in the end, it turned out that the taxpayers mostly won the cases. To that end, this paper seeks to analyze the transfer pricing audit performance in Indonesia based on 2021’s Tax Court Decree. This allows us to know what factor(s) contributed to the transfer pricing dispute and how the tax court settled the dispute. As a practical implication, it is suggested that state revenue agencies improve the quality of their transfer pricing tax audit performance.